Preoperative Prognostic Nutritional Index Predict Survival in Patients With Resectable Esophageal Squamous Cell Carcinoma - Zheng, Zhiwei; Zhu, Huide; Cai, Hongfu (Frontiers in Nutrition, 2022)
Background: Prognostic nutritional index (PNI) index is a nutritional evaluation index put forward by Japanese scholar Onodera, which has been widely applied to evaluate the prognosis of cancer.. This study aimed to evaluate the PNI on predicting the overall survival (OS) in resectable esophageal squamous cell carcinoma (ESCC). Methods: 165 resectable ESCC patients were included in our retrospective study. PNI values before surgery were calculated for each patient[PNI = 10 x Albumin (gr/ dL) + 0,005 x Total lymphocyte count (mm3)]. PNI cutoff value was selected by drawing ROC curve used overall survival time as the end point. Kaplan-Meier method and Cox regression model of multivariate analysis were used to analyze the prognostic relationship between PNI and overall survival (OS).Results: Among the 165 patients, 34 (20.60%) were women and 131 (79.40%) were men. The mean age was 62.67±7.95 years, with the age range from 44 to 85 years. The average PNI were 46.68 ± 8.66. ROC curve showed the best cutoff value was 43.85 and all patients were divided into two groups,72 patients (43.6%)were in low PNI group (<43.85) while 93 patients (56.4%) were in high PNI group (≥43.85). Univariate analysis demonstrated that PNI, tumor length, and T-stage and pathological stage were related to the prognosis of ESCC patients (P < 0.05).The Kaplan-Meier curve showed that high PNI group was significantly increase the OS compare low PNI group (p=0.01 ). Three year OS rates were 57.5% in low PNI group while 77.7% in high PNI group. Univariate analysis showed that advanced pathological stage, large tumor length, and low PNI(separately,p<0.05) were as significant risk factors for shorter OS. Multivariate analysis showed that tumor length (P = 0.008) and PNI (P =0.017) were independent prognostic factors in patient with resectable ESCC. Conclusion: PNI is a simple and useful predictive marker of for the overall survival time in patients with radical esophagectomy.